PENINGKATAN KUALITAS DAN MUTU PENDIDIKAN AGAMA HINDU MELALUI PEMAHAMAN TAKSONOMI TRI KAYA PARISUDHA - Parmajaya, I Putu Gede (LPM IHDN Denpasar, 2016)
With the development aspects of psychology including psychological study, through many discussion groups, came the thoughts more carefully. In psychology study clearly a critical component that needs high attention also besides the cognitive aspects, in particular cognitive processes. Important aspects or components of it are the components of knowledge or knowledge learned. Each knowledge or science has important characteristics to consider in studying it. There may be the same traits in two different sciences, even though not all the same characteristics. In Hindu religious subjects, for example, many objects are abstract and immediate assessment using deductive reasoning. At this time has successfully developed a rich taxonomy of value-based tri kaya parisudha by Parmajaya, taxonomy was named Taxonomy Tri Kaya Parisudha. Taxonomy is expected to be used as a measurement of psychological for teachers to gauge the level of bhakti sradha (belief and trust) Hindu students